Adaptation and Validation of the Indonesian Version of the Environmental Cynicism Scale - Muhammad Niam Makhali; Mutmainnah Mutmainnah; Andi Ariani Reski Ramadana Putri Tanjung; Ratna Jatnika; Rahmad Muliadi (Jurnal Ecopsy, 2026)
Environmental cynicism refers to distrust of the motives underlying environmental conservation efforts. In Indonesia, research on this phenomenon remains limited, largely because no instrument has been systematically adapted for the local context. Following the International Test Commission (ITC) guidelines, this study translated and adapted the Environmental Cynicism Scale (ECS) for use in Indonesia. University students were recruited through convenience sampling. The adaptation process included forward-backward translation, expert evaluation of content validity, and assessment of response process validity to ensure alignment with the intent of the original instrument. The findings showed that the ECS items were relevant and easy for respondents to understand. Confirmatory factor analysis supported a unidimensional measurement model, with acceptable factor loadings and satisfactory internal consistency. The Indonesian version of the ECS, which consists of six items, was valid and reliable for assessing environmental cynicism among university students in Indonesia. These findings provide a foundation for using the ECS in Indonesian environmental psychology research and offer directions for future studies on factors that shape individual engagement with environmental issues.